1975
DOI: 10.1042/cs0480239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Erythrocyte Membrane Ouabain-Sensitive Adenosine Triphosphatase after Renal Transplantation

Abstract: 1. Intracellular electrolytes, and erythrocyte membrane adenosine triphosphatase (ATPase) activity, was studied in twenty patients after renal transplantation. 2. The mean ouabain-sensitive ATPase activity in the erythrocyte membranes of the transplant patients was 122 nmol of inorganic phosphorus (Pi) h-1 mg of tissue-1 (SEM 14), compared with 62 nmol of Pi h-1 mg of tissue-1 (SEM 8) in a group of paired, healthy controls. 3. The increase in ouabain-sensitive ATPase was most marked in the 4 months after trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

1977
1977
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
2
4
2
Order By: Relevance
“…The present results obtained by the 86Rb uptake method are consistent with this finding and suggest that a similar alteration of Na+, K'-ATPase activity occurs in patients with ARF. In patients with previous CRF treated by renal transplantation, Cole and Maletz [4] and Cole et al [5] reported increased Na+, K+-ATPase activity, which con trasts with our results which did not show any difference in 86Rb uptake between these patients and paired controls.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The present results obtained by the 86Rb uptake method are consistent with this finding and suggest that a similar alteration of Na+, K'-ATPase activity occurs in patients with ARF. In patients with previous CRF treated by renal transplantation, Cole and Maletz [4] and Cole et al [5] reported increased Na+, K+-ATPase activity, which con trasts with our results which did not show any difference in 86Rb uptake between these patients and paired controls.…”
Section: Discussionsupporting
confidence: 79%
“…Dransfield and Greff [6] reported that prednisone could alter in vitro Na% K -ATPase activity in RBC. But this does not provide an explanation for the discrepancy between our results and those of Cole and Maletz [4] and Cole et al [5] whose patients were also taking prednisone and azathio prine.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It has been reported that erythrocyte membrane Na,K-ATPase activity is supranormal in renal transplant patients [24], and that erythrocyte Na content is normal or low [13,25], Ion flux studies suggest that Na,K pump function in transplanted patients is normal or increased [5,25]. In the present experiments, erythrocytes from these patients had normal membrane transport, ouabain binding properties and intracellular sodium concentra tions.…”
Section: Patients With Functional Transplantssupporting
confidence: 51%
“…Cole and Maletz (37) reported decreased erythrocyte sodium and increased Na-K ATPase in renal transplant recipients, and observed that the changes were the obverse of those reported in uremia. In light of the findings presented here, it appears likely that the findings described in transplant recipients were, in large part, due to the administration of prednisone in those patients.…”
Section: Resultsmentioning
confidence: 91%